Assessment of metal exposure (uranium and copper) in fatty acids and carbohydrates profiles of Calamoceras marsupus larvae (Trichoptera) and Alnus glutinosa - Tagliaferro, Marina Beatriz (2022)
Physiological changes were explored in fatty acids (FA) and carbohydrate (CHO) composition in the shredder Calamoceras marsupus larvae (Trichoptera) and leaf litter (C. marsupus food) exposed to copper and uranium under natural and experimental conditions. We measured FA and CHO content in leaf litter and larvae specimens from reference and impacted streams, and exposed for 5 weeks to four realistic environmental concentrations of copper (35 μg L−1 and 70 μg L−1) and uranium (25 μg L−1 and 50 μg L−1). Regarding FA, (1) leaf litter had a reduced polyunsaturated FA (PUFA) content in metal treatments, s (14 to 33% of total FA), compared to natural conditions (≥39% of total FA). Leaf litter exposed to uranium also differed in saturated FA (SFA) composition, with lower values in natural conditions and higher values under low uranium concentrations. (2) C. marsupus had/showed low PUFA content under Cu and U exposure, particularly in high uranium concentrations. Detritivores also decreased in PUFA under exposure to both metals, particularly in high uranium concentrations. On the other hand, (1) microorganisms of the biofilm colonizing leaf litter differed in CHO composition between natural (impacted and reference) and experimental conditions, with glucose and galactose being consistently the most abundant sugars, found in different amounts under copper or uranium exposure; (2) CHO of detritivores showed similar high galactose and fucose concentrations in contaminated streams and high copper treatments, whereas low copper treatment showed distinct CHO profiles, with higher mannose, glucose, arabinose, and fucose concentrations. Our study provides evidence of metal exposure effects on FA and CHO contents at different trophic levels, which might alter the quality of food flow in trophic webs